2015
DOI: 10.1016/j.renene.2015.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Do the Spanish want biodiesel? A case study in the Catalan transport sector

Abstract: 7In this paper, we analyse the opinions, attitudes and willingness of consumers to pay for 8 biodiesel as an alternative to diesel in Barcelona province. Data were gathered from face-to-9 face structured questionnaires from 300 diesel car owners/users that regularly purchase fuel. 10 A variation of the traditional choice experiments (CE) was used by excluding the price attribute 11 from the design. In a subsequent contingent valuation (CV) exercise, respondents were asked 12 to state their maximum willingness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
(11 reference statements)
2
3
0
Order By: Relevance
“…On the other hand, the majority of drivers are not worry about the influence of the biodiesel in the power, consumption and cost of maintenance of the car. This result is in line with Kallas and Gil (2015) who found for Catalonian drivers that biodiesel availability in petrol stations is the most important reason of not using biodiesel. On contrary, results differ from Giraldo et al (2010) who found that the most important reasons preventing the use of biodiesel are the lack of information about the product and about the effect it may have on the car engine.…”
Section: Survey Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, the majority of drivers are not worry about the influence of the biodiesel in the power, consumption and cost of maintenance of the car. This result is in line with Kallas and Gil (2015) who found for Catalonian drivers that biodiesel availability in petrol stations is the most important reason of not using biodiesel. On contrary, results differ from Giraldo et al (2010) who found that the most important reasons preventing the use of biodiesel are the lack of information about the product and about the effect it may have on the car engine.…”
Section: Survey Resultssupporting
confidence: 92%
“…On the other hand, only 0.2 percent (one respondent) indicated that he/she always used biodiesel and 12 percent stated that use biodiesel often or sometimes. This actual frequency of use is similar to Kallas and Gil (2015) for drivers in Cataluña (other northeast region in the Iberian Peninsula east of Aragon). Respondents were asked the reasons for not using biodiesel (Table 2) and the main reason of not using it is the lack of availability in the regular petrol station.…”
Section: Survey Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…However, its integration into the world energy market remains predominantly weak, being less than 13% worldwide [6]. Biodiesel continues to be the highest production biofuel in the world, and the European Union is the largest producer, where 70% of biofuel is produced for the transport sector [7]. Developing countries are highly dependent on imported fossil fuels such as diesel and simultaneously face the challenge of reducing their greenhouse gas emissions [8].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Despite great achievements made, the current TWCs still suffer from the relatively high ignition temperature and poor hydrothermal stability that cannot match the increasingly powerful engines, as well as the stricter and stricter emission regulations. [7,8] To this end, the nature of TWCs, involving compositions, sizes, shapes, and interactions between metals and supports, must be elaborately manipulated, and new optimization mechanisms for catalytic-performance promotion are highly desired. [9][10][11] Recently, single-atom catalysts (SACs) have received much attention owing to the maximized metal dispersity and utilization efficiency, which paves a new to cut costs of the current TWCs.…”
mentioning
confidence: 99%